The seismic SPT test in a tropical soil and the G(0)/N ratio - Giacheti, H. L. [UNESP]; Pedrini, R. A. A. [UNESP]; Rocha, B. P.; Delage, P.; Desrues, J.; Frank, R.; Puech, A.; Schlosser, F. (Presses Des Ponts, 2013)
The seismic SPT, a test which associates the up-hole technique to the SPT, is briefly described. The maximum shear modulus (Go) can be determined together with the N value with this hybrid test. Seismic (Cross-hole, Down-hole and SCPT) and SPT test data for a Brazilian tropical sandy soil are presented and discussed emphasizing the advantage of using the interrelationship between the small strain stiffness (Go) and an ultimate strength (N value) to identify different soil behavior. A seismic SPT test was carried out in this research site and the Go/N ratio is discussed as an interesting index to help characterize tropical soils, similar to what has been suggested for the Go/qc ratio determined in a single test.
Keywords: In situ testing; SPT; seismic; up-hole; tropical soil; Go/N ratio